Biomolecules with Antioxidant Capacity from the Seeds and Sprouts of 20 Varieties of Chenopodium quinoa Willd. (Quinoa) - Edwin Carlos Enciso-Roca (MDPI AG, 2021)
Quinoa has acquired a great interest due to its high content of nutrients and biomolecules that have nutritional and medicinal properties. The aim of this study was to compare the total phenolic content (TPC), total flavonoids (TF), and the antioxidant capacity of 20 varieties of seeds and sprouts of quinoa extract. Quinoa seeds were germinated for 72 h and dried in an oven at 45 °C. The extracts were obtained by dynamic extraction using methanol. Phytochemical analysis with liquid chromatography coupled with mass spectrometry (LC-ESI-MS/MS), TPC, TF, and the antioxidant capacity was carried out and compared between both extracts. The TPC was determined with Folin-Ciocalteu reagent, TF with AlCl3, and the antioxidant capacity was determined according to the DPPH and ABTS assays. Sprout extracts showed high values of TPC (31.28 ± 0.42 mg GAE/g; Pasankalla variety), TF (14.31 ± 0.50 mg EQ/g; black Coito variety), and antioxidant capacity (IC50 (DPPH): 12.69 ± 0.29 µg/mL and IC50 (ABTS): 3.51 ± 0.04 µg/mL; Pasankalla). The extracts of the Pasankalla variety revealed 93 and 90 phytochemical constituents in the seeds and sprouts, respectively, such as amino acids, phenolic acids, flavonoids, fatty acids, and triterpene saponins, among others. Quinoa sprouts showed a high content of TPC and TF, and high antioxidant capacity compared with seed extracts, especially the Pasankalla variety.